Diagnosis and Management of Polyorchidism: A Case Report and Literature Review - Anthony Kanbar; Charbel Dabal; Joey El Khoury; Rami Halabi; Serge Assaf; Anthony Mina; Sabine Breidi; Maher Abdessater; Raghid El Khoury (Case Reports in Urology)
Polyorchidism, or supernumerary testis, is a rare congenital abnormality of the genitourinary system. In this paper, we present the case of triorchidism in a seven-year-old asymptomatic child with a suspect left scrotal mass detected on routine physical examination. Imaging studies revealed a third testicle in the left hemiscrotum, with comparable dimensions, signal intensity on MRI, and Doppler flow on ultrasound with the ipsilateral testis. We also discuss the clinical presentations, classifications, and current diagnostic and therapeutic strategies of this condition.